Polish Independent Press Summary, no. 46 (1989) - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
A digest of Polish underground press (including articles, tables of content, and book covers) compiled by members of the RFE Polish Underground Publications Unit to be used in a daily 20-minute broadcast on Polish samizdat. Extract from Przegląd Wiadmości Agencyjnych, no. 41 (9 December 1988). Extract from Robotnik, no. 7(139) (6 December 1988). Extract from KOS, no. 150 (11 December 1988). Table of Contents from Kurs, no. 37 (November 1988). Extract from Kurs, no. 37 (November 1988). Table of Contents from Obóz, no. 14 (1988). Table of Contents from Kontur - Kwartalnik Literacki, no. 1 (1988). Table of Contents from Contra, no. 1/2 (1988). Extract from Contra, no. 1/2 (1988). Cover Page from Misztalski, Marian. Gdzie ja jestem ?: Zapiski wewnętrzne emigranta albo Pamiętnik okresu przejrzewania. [Łódź ; Warszawa]: Kurs, 1988.